1984
DOI: 10.1159/000249691
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Fibroblast and Dermis Fibroblast Activation by Laser Irradiation at Low Energy

Abstract: The effects of laser irradiations have been estimated both from the clinical point of view (rate of reduction of the ulcerated area) and in ultrastructural terms. The modification produced by laser in human fibroblasts in culture have also been investigated. Under our clinical and experimental conditions, laser stimulates the secretion of fibroblasts, both in vivo and in vitro, for reasons that are still the object of research. After irradiation the formation of periodic collagen fibrils is not observed, so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
6

Year Published

1985
1985
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 0 publications
3
26
0
6
Order By: Relevance
“…In this work, Hardy et al [29] reported a five-fold increase in the number of fibroblasts exposed to four 10.0 J cm -2 doses of pulsed ruby laser when compared to controls that were not treated with laser light. Subsequent studies have since shown that the increased proliferation of fibroblasts results in increased collagen synthesis in vitro as well as in vivo [30][31][32][33][34][35][36][37][38]. For example, a total of 4.0 joules laser energy applied on experimentallyinduced skin incisions [39] or skin defects in rats [30], produces faster collagen synthesis as judged by assaying 14 C glycine and 3H proline or 3H hydroxyproline [30,39].…”
Section: Effects Of Laser Photostimulationmentioning
confidence: 99%
“…In this work, Hardy et al [29] reported a five-fold increase in the number of fibroblasts exposed to four 10.0 J cm -2 doses of pulsed ruby laser when compared to controls that were not treated with laser light. Subsequent studies have since shown that the increased proliferation of fibroblasts results in increased collagen synthesis in vitro as well as in vivo [30][31][32][33][34][35][36][37][38]. For example, a total of 4.0 joules laser energy applied on experimentallyinduced skin incisions [39] or skin defects in rats [30], produces faster collagen synthesis as judged by assaying 14 C glycine and 3H proline or 3H hydroxyproline [30,39].…”
Section: Effects Of Laser Photostimulationmentioning
confidence: 99%
“…Investigations have proved that the He-Ne laser irradiation of 25-mW output had a direct influence on human fibroblasts of 32nd passage (Bosatra et al, 1984). The synthesis of fibrillar material was stimulated, but collagenogenesis was not influenced.…”
Section: Action On Proliferative Activitymentioning
confidence: 99%
“…PGE 2 injection causes local pain and severe root resorption [4], and frequent injections of 1,25-(OH) 2 D 3 or PTH may induce unfavorable general conditions. Recently, various biostimulatory effects of lowenergy laser irradiation that involve wound healing [5][6][7], fibroblast [8][9][10][11] and chondral proliferation [12], collagen synthesis [13][14][15][16], and nerve regeneration [17] have been reported. In particular, the acceleration of bone regeneration by laser treatment has been a focus of contemporary research [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%